Rare case of Hirayama’s disease - Gala, Rohan Bharat; Vyas, Sudhanshu Rakesh; Dhond, Amit B.; Shah, Akshay Hemant; Khedekar, Ravindra G.; Shetty, Sunil H. (International Journal of Research in Medical Sciences, 2017)
Hirayama’s disease is a rare benign neurological disorder also known as monomelic amyotrophy, Sobue disease,Juvenile Muscular Atrophy of Distal Upper Extremity (JMADUE). It mainly affects young males in their second or third decades and is most commonly seen in Asian countries like Japan, Malaysia and India. In majority of the cases the cause of the disease is unknown. An 18 year male came with weakness in his right hand and forearm since 1 year. Examination revealed weakness and wasting of muscles of forearm and hand without lower limb involvement and normal deep tendon reflexes. MRI showed focal short segment hyperintense signal in the ventral and right lateral aspect of the cervical cord at C5-C6 level with the involved segment measuring 4x3mm in size. Based on clinical and radiological features a diagnosis of focal amyotrophy was made. Patient is given a cervical collar to prevent flexion at the neck and physiotherapy in the form of hand and forearm exercises were started. Regular follow up of the patient once every 2 months is being done. Hirayama’s disease is a rare, benign, self-limiting neurological disorder. Early diagnosis and management by preventing cervical flexion with the help of a cervical collar has shown to halt the progression of the disease.